Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1038/hr.2010.230
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of activated prorenin in the pathogenesis of slowly progressive nephropathy in the non-clipped kidney of two kidney, one-clip hypertension

Abstract: The handle region peptide (HRP), a (pro)renin receptor (P)RR blocker, did not prevent the acute nephropathy occurring 2 weeks after clipping in renovascular hypertensive rats. This study was performed to examine the effects of HRP, its scramble peptide, or a saline vehicle on slowly progressive nephropathy occurring in the kidneys of two-kidney, one-clip Goldblatt hypertensive rats. At 2 weeks after clipping, the renal morphology in the clipped and non-clipped kidneys was similar in the three groups of rats. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
4
3
Order By: Relevance
“…However, in apparent contrast with the above in vitro results on glucose-induced (P)RR upregulation in mesangial cells, HRP (0.2 mg/kg of body weight per day) did not suppress the elevated renal interstitial AngII in diabetic rats, nor normalized the increased (P)RR expression in this model [88]. In fact, the lack of effect of HRP on (P)RR expression appears to be a general phenomenon in in vivo studies applying this drug [76,78,[89][90][91]. AT 1 receptor blockade with valsartan did normalize (P)RR expression, and both HRP and valsartan suppressed the up-regulated TGFβ1 levels in the diabetic rat kidney [92].…”
Section: Kidney and Diabetescontrasting
confidence: 83%
See 1 more Smart Citation
“…However, in apparent contrast with the above in vitro results on glucose-induced (P)RR upregulation in mesangial cells, HRP (0.2 mg/kg of body weight per day) did not suppress the elevated renal interstitial AngII in diabetic rats, nor normalized the increased (P)RR expression in this model [88]. In fact, the lack of effect of HRP on (P)RR expression appears to be a general phenomenon in in vivo studies applying this drug [76,78,[89][90][91]. AT 1 receptor blockade with valsartan did normalize (P)RR expression, and both HRP and valsartan suppressed the up-regulated TGFβ1 levels in the diabetic rat kidney [92].…”
Section: Kidney and Diabetescontrasting
confidence: 83%
“…HRP (3.5 ÎĽg/kg of body weight per day during 14 days) did not affect hypertensive nephrosclerosis in Goldblatt (2K1C) rats [102]. Ryuzaki et al [91], when applying HRP at 1 mg/kg of body weight per day in 2K1C rats, confirmed this finding, but simultaneously demonstrated that HRP after 12 weeks of infusion reduced the glomerulosclerosis index, tubulointerstitial damage, TGFβ1 expression and AngII levels in the nonclipped kidney (but not in the clipped kidney). Under no condition did HRP affect BP or proteinuria.…”
Section: Kidney and Diabetesmentioning
confidence: 99%
“…In contrast, the long-term treatment with HRP prevents the glomerular and tubular damage that develop chronically in the non-clipped kidneys in the 2K1C models. In other words, the only difference between the previous report 20 and the study done by Ryuzaki et al 22 is simply in the longer duration of administration of HRP in the Goldblatt hypertensive model, which suggests that the effect of HRP was dependent on the treatment length, but not on the dosage of HRP. In contrast to aliskiren, because HRP did not reduce the blood pressure, the effect of HRP is only expected in chronic administration and therefore was not observed in the acute phase of the Goldblatt hypertensive model.…”
contrasting
confidence: 51%
“…19 There is much confusion concerning the mode of action of HRP, and the basis of the discrepancy between the in vitro and in vivo data is unknown. Overall, the HRP results in the animal models were disappointing, although Ryuzaki et al 22 clearly showed beneficial effects of HRP in the two-kidneys, one-clip (2KIC) model of hypertensive nephrosclerosis in an issue of Hypertension Research. They carefully investigated the long-term effect of HRP on the slowly progressive nephropathy that occurred in the nonclipped kidney of the two-kidneys, one-clip renovascular hypertension model.…”
mentioning
confidence: 99%
“…These controversies may be explained by the prorenin-renin ratio since the decoys were effective in high prorenin/low renin models (1,11), and/or by the length of treatment based on the observation that renoprotective effects were able to be observed after 12 weeks even in a high renin Goldblatt model (12,13). …”
Section: Introductionmentioning
confidence: 99%